The Migration of Javanese Poetry Writers from Print into Digital Media - Joe Harrianto Setiawan (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
Literature is an important part of a nation's civilization. Local literature also contributes to the transmission of local values from one generation to the next. So far, written literature has been printed and disseminated through print media and also in sections in print media such as magazines and newspapers. Including the publication of Javanese poetry in local media. However, as of now, the disruptive era has forced some print media publications to close, while others have migrated online. Javanese poetry writers must also find new ways to create their work online. The research method used was descriptive qualitative by conducting interviews with Javanese poetry artists who are members of the Paguyuban Panotocoro Yogyakarta. Media adaptation involves a system's ability to adjust to users' behaviors or environmental changes. The challenge that traditional Javanese artists face when migrating to the internet era is their lack of understanding of technology. Additionally, a significant issue confronting Javanese poets as they transition to the digital age lies in the shift required by the internet’s audio-visual technology. This shift demands that the traditional written format be transformed into audio or video formats. The research findings reveal that the digitization of Javanese poetry has, in a way, returned it to its original form, where it was traditionally performed as tembang or songs. Tembang, as a form of oral communication, served as the primary means through which Javanese people conveyed messages before they adopted writing systems and lettered scripts. This mode of delivering messages in a peaceful and fluid setting allows the moral messages within the poetry to be easily absorbed and internalized in people’s lives.